Subjective well-being and influencing factors in Turkish nursing students: A cross-sectional study - Suleyman Umit Senocak; Fatma Demirkiran (Journal of the Pakistan Medical Association, 2020)
Objective: To investigate subjective well-being levels of nursing students and the factors affecting it. Methods: The cross-sectional descriptive study was conducted at a health school of a state university in Aydin, western Turkey, from March to April, 2015, and comprised nursing students in the bachelor’s programme. Personal information form, perceived stress scale, perceived social support scale, subjective well-being scale were used for data collection. Multiple linear regression analysis with stepwise method was employed using SPSS 18 for data analysis. Results: Of the 297 subjects, 230(77.4%) were female. The overall mean age of the sample was 20.32±1.65 years. Perceived stress, perceived social support, participation in social or cultural activities, perception of academic success and conscious choice of nursing career accounted for 54% of the variance in the students’ subjective wellbeing and it is a useful model. Perceived stress alone accounted for 39% of the variance. However, students’ perceptions of economic status and availability of teachers with whom students could share their problems did not explain subjective well-being in the model. Conclusion: Perceived stress was found to play an important role in subjective well-being of the nursing students. Keywords: Subjective well-being, Stress, Social support, Nursing students.